Legal Frameworks for Carbon Taxation: A Comparative Study of Indonesia and Japan - Muhammad Asrul Maulana; Savira Aristi (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2025)
Introduction: The comparison of carbon tax regulations between Indonesia and Japan is highly relevant, considering that Japan has implemented a carbon tax policy earlier, on a larger scale, and with varying rates for different types of carbon emissions. By analyzing this comparison, Indonesia is expected to identify a more effective approach to reducing carbon emissions without hindering economic growth. Purposes of the Research: The purpose of this legal comparison is to evaluate and propose a unification of carbon tax policies in Indonesia that better align with domestic conditions and needs, by taking into account the experiences of other countries, particularly Japan. This unification aims to create a more efficient and equitable carbon tax system that can support Indonesia’s efforts in achieving its carbon emission reduction targets This unification aims to create a more efficient and equitable carbon tax system, and can support Indonesia's efforts to meet its carbon emission reduction targets. Methods of the Research: This study uses a normative method with a comparative approach. The primary legal material used is a comparison between the Indonesian legal framework and the Japanese legal framework. Comparative analysis is focused on law in the context by using a micro approach, i.e. a comparison of legal norms. Results Main Findings of the Research: This research contributes to the legal and policy discourse on carbon taxation by providing a comparative analysis between Indonesia and Japan, focusing on how regulatory design and economic instruments can balance environmental goals with industrial competitiveness. The study finds that while Japan’s carbon tax operates within a mature regulatory framework supported by strong institutional coordination and public compliance, Indonesia’s system remains at a formative stage, requiring detailed implementing regulations and clear emission accounting mechanisms. Both countries share the objective of promoting low-carbon transitions, but differ in tariff structure, policy maturity, and economic adaptability. Japan’s experience demonstrates that consistent policy enforcement and alignment with renewable energy incentives enhance effectiveness, a lesson Indonesia can adopt to balance environmental protection with sustainable economic growths.